Clinical companion to medical-surgical nursing - Dirksen, Shannon Ruff. (Mosby, 2004)
This clinical manual presents approximately 200 commonly encountered medical-surgical disorders and procedures in a concise, alphabetical format for quick clinical reference. Designed for portability, the Clinical Companion includes the essential, need-to-know information for medical-surgical nursing practice. The attractive and functional two-color design highlights key information, and helpful cross-references to the Lewis text direct students to more extensive background information. The 3rd edition features expanded patient and family teaching content as well as additional illustrations and tables to enhance functionality and visual appeal